2022
DOI: 10.1186/s13007-021-00836-0
|View full text |Cite
|
Sign up to set email alerts
|

An advanced method for the release, enrichment and purification of high-quality Arabidopsis thaliana rosette leaf trichomes enables profound insights into the trichome proteome

Abstract: Background Rosette leaf trichomes of Arabidopsis thaliana have been broadly used to study cell development, cell differentiation and, more recently, cell wall biogenesis. However, trichome-specific biochemical or -omics analyses require a proper separation of trichomes from residual plant tissue. Thus, different strategies were proposed in the past for trichome isolation, which mostly rely on harsh conditions and suffer from low yield, thereby limiting the spectrum of downstream analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 90 publications
(108 reference statements)
1
25
0
Order By: Relevance
“…Metabolomic profiling, however, requires an altered buffer composition during trichome release, as sample preparation for metabolomics requires the quenching of metabolic processes, for instance, by cold methanol (de Jonge, Douma, Heijnen, & van Gulik, 2012). Lastly, we note that the EDTA‐based trichome release protocol described here is applicable to plant species other than A. thaliana , including N. benthamiana (tobacco) and S. lycopersicum (tomato) (Huebbers et al., 2022). However, the exact amount of deployed plant mass and the time frame for agitation in EDTA‐PBS buffer requires optimization for specific plant species.…”
Section: Commentarymentioning
confidence: 99%
See 4 more Smart Citations
“…Metabolomic profiling, however, requires an altered buffer composition during trichome release, as sample preparation for metabolomics requires the quenching of metabolic processes, for instance, by cold methanol (de Jonge, Douma, Heijnen, & van Gulik, 2012). Lastly, we note that the EDTA‐based trichome release protocol described here is applicable to plant species other than A. thaliana , including N. benthamiana (tobacco) and S. lycopersicum (tomato) (Huebbers et al., 2022). However, the exact amount of deployed plant mass and the time frame for agitation in EDTA‐PBS buffer requires optimization for specific plant species.…”
Section: Commentarymentioning
confidence: 99%
“…However, the exact amount of deployed plant mass and the time frame for agitation in EDTA‐PBS buffer requires optimization for specific plant species. Helianthus annuus (sunflower), for instance, provided a comparably low yield of 3.89 mg g ‐1 trichome fresh mass per harvested leaf mass (Table 1), and microscopy of processed leaves revealed that a considerable amount of trichomes remained attached to the leaf surface during the release step (Huebbers et al., 2022).…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations